PERLINDUNGAN HAK TERSANGKA DALAM PROSES PENYIDIKAN DITINJAU DARI ASPEK PSIKOLOGI HUKUM: PROTECTION OF THE RIGHTS OF SUSPECTS IN THE PROCESS OF INVESTIGATION FROM LEGAL PSYCHOLOGICAL ASPECTS - Zakariah, Fadil Rahmat; Mas, Marwan; Oner, Basri (Clavia, 2022)
This study aims to determine the protection of the suspect's rights in the investigation process in terms of the psychological aspects of the applicable law, so that this problem can be answered clearly both in theory and practice orbdirect observationeinnthenfield. Thiseresearchtwaseconductedeat the Resort Police Office (POLRES) Maros, thefresearch .methodwusediisqa normative researchtmethodothat uses data collectionctechniques, interviews and literature9studies to analyze data using descriptive analysis methods. The resultskof.the study sindicate that in the psychological.aspectkof the investigation, both the investigator and the suspect in providing clear and free information are implemented in Article 50 of the Criminal Procedure Code concerning the Protection of the Rights of Suspects during the Investigation Process. In connection with the objectives of the KUHAP above, in an effort to find material truth in the investigation process by investigators, a suspect or defendant has rights that must be protected by law, namely, the right to receive an immediate examination, the right to make a defense, the right to give information freely and without pressure, the right to legal aid, the right to choose one's own legal counsel, the right to present witnesses, the right not to be burdened with the obligation of proof, the right to visit family and relatives during detention, the right to be tried in a trialsopen too the public, the right to receive compensation and rehabilitation. In relation to the criminal psychology aspect of the suspect, it was during the detention period and the interrogation process felt by the suspect who was interviewed. The suspect personally felt anxious about other suspects and clearly had a psychological impact on him while in detention due to being the only female detainee available.